2020
DOI: 10.2459/jcm.0000000000000907
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnostic ECG criteria for left ventricular hypertrophy: is it time to change paradigm in the analysis of data?

Abstract: Background Twelve-lead ECG represents the most common diagnostic tool in clinical cardiology and allows an immediate screening of left ventricular hypertrophy (LVH), but current criteria might have poor clinical usefulness in everyday clinical practice due to lack of sensitivity. Methods The current study aims to review and compare the clinical performance of known ECG criteria of LVH in a real-life setting; 2134 patients had ECG and echocardiographic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A novel ECG criterion for LVH, proposed by Peguero et al [11], was recently shown to be more sensitive than traditional ECG-LVH criteria in patients with arterial hypertension. To date, the ability of the novel criterion to discriminate patients with and without anatomic LVH have been estimated in various clinical settings, including cardiac patients and the general population, demonstrating generally rather modest (and, at best, moderate) superiority over the classical ECG-LVH criteria in some [12][13][14][15][16], but not all [17][18][19][20][21][22][23]. However, to the best of our knowledge, only one study was focused on patients with aortic stenosis [24], the most prevalent valvular heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…A novel ECG criterion for LVH, proposed by Peguero et al [11], was recently shown to be more sensitive than traditional ECG-LVH criteria in patients with arterial hypertension. To date, the ability of the novel criterion to discriminate patients with and without anatomic LVH have been estimated in various clinical settings, including cardiac patients and the general population, demonstrating generally rather modest (and, at best, moderate) superiority over the classical ECG-LVH criteria in some [12][13][14][15][16], but not all [17][18][19][20][21][22][23]. However, to the best of our knowledge, only one study was focused on patients with aortic stenosis [24], the most prevalent valvular heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this hypertensive cohort, the Cornell voltage criterion showed the highest area under the ROC curve (0.60), outperforming GU and SKL voltage criteria. Similarly, Ricciardi et al demonstrated that the Cornell voltage criterion had superior diagnostic performance compared to RaVF amplitude and the Peguero-Lo Presti criterion [ 21 ]. Likewise, Park et al found Cornell voltage to have better performance over the SKL voltage criterion in their study of 332 Koreans [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the Sokolow-Lyon voltage criteria for recognition of LVH were the weakest, which is in line with other studies. Elffers et al [31] showed that discriminative performance of the Sokolow-Lyon voltage criteria is poor (AUC: 0.58) in obese individuals, while Ricciardi et al [62] showed that the Cornel voltage and Cornel product criteria have a more accurate diagnostic performance compared with other hospitalized patients. Courad et al [63] suggested that the R wave in a VL lead should be the first index used to detect LVH of hypertensive patients, and it should replace the Sokolow-Lyon index due to the latter's inadequacies.…”
Section: Electrocardiographic Indicatorsmentioning
confidence: 99%